Gross motor proficiency deficits among children and adolescents post posterior fossa brain tumor removal vs. traumatic brain injury in the chronic phase of recovery: a cross-sectional study - Barak, Sharon; Brezner, Amichai; Yissar, Tamar; Eisenstein, Etzyona; Ackerman-Laufer, Shirley; Landa, Jana (Frontiers in Sports and Active Living, 2024)
Introduction: Acquired brain injury (ABI) is a prevalent diagnosis in pediatric rehabilitation. Gross motor skills are often affected by ABI and limit the ability to participate in various physical activities. However, as ABI injury location is diverse, children and adolescents (youth) with localized ABI, such as ABI in the posterior fossa (ABI-PF) may present unique and different motor disabilities than youth with ABI on account of traumatic brain injury (TBI). Aims: The aims of the study were: 1) to compare gross motor deficits in youth with TBI versus ABI-PF; and 2) to compare two methods on scoring BOT2 to determine which is better for identifying motor deficits. Methods: Participated in this study youth with TBI (N=50) and ABI-PF (N=30). Participants were tested on Bruininks-Oseretsky Test of Motor Proficiency-2nd Edition (BOT2) Upper-Limb Coordination, Balance, Strength, Running Speed and Agility, and Bilateral-Coordination subtests. Motor performance deficits were established using two-standard deviations (2SD) and age-equivalent methods. Between-group differences were assessed via independent t-tests and receiver operating characteristic curves (ROC). Results: According to the 2SD method, motor deficits in the ABI-PF group ranged from 20%-66.66%, whereas in the TBI group 8%-16%. According to the age-equivalent method, in the TBI and ABI-PF groups 40%-66.0% and 46.66%-76.66% of the youth presented motor deficits, respectively. Moreover, ROC analysis showed that motor performance deficits of both groups in all sub-scales except for Bilateral Coordination differed enough to result in medium area under the curve. Conclusions: Motor deficits post-pediatric ABI are prevalent. In comparison to the TBI group, deficits are greater in the ABI-PF group. Moreover, compared to the 2SD method, the extent of motor deficiency is greater in the age-equivalent method. Therefore, using the later might provide a more valid classification of deficits in gross motor proficiency for youth post-ABI.